"If It Hadn't Been Online I Don't Think I Would Have Applied": Applicant Experiences of an Online Family Violence Intervention Order Process. Issue 1 (January 2022) - Ross, Stuart; Aitken, Sophie
Domestic violence protection orders are civil court orders intended to protect victim/survivors from further violence by prohibiting alleged perpetrators from engaging in threatened or actual violence or harassment of victim/survivors and their children. However, their availability and ultimately their effectiveness is limited by complex procedural requirements and court accessibility barriers that victim/survivors can find intimidating, confusing, and unsafe, and that contribute to delays between lodgment of an application and the making of an intervention order by the court. This study examined the experiences of applicants who used either a conventional court process or an online application process that was trialed in three courts in Victoria, Australia. We examined court data on 791 applicants who sought an intervention order at the three courts during the study period, and interviewed 28 applicants including 12 who had applied online. We also examined the impact of the online process on court workloads and risk assessments, and conducted interviews and focus groups with magistrates and registry staff at each of the three trial locations. Compared with the court registry process, the online application was rated as simpler and easier to understand and less stressful. Online applicants also reported that the application process was more accessible and enhanced their sense of agency. The online application process also reduced the workload of court staff and resulted in faster case processing, with online applicants reaching the court hearing stage nearly 2 weeks earlier than paper-based applicants. However, we did not find that the online application process provided earlier or better risk identification.